Pengaruh Good Corporate Governance, Transfer Pricing, Earnings Management Terhadap Tax Avoidance Dengan Profitability Sebagai Variabel Moderasi - Yogi Permani; Hari Setiono; Nurdiana Fitri Isnaini (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims to test the board of directors, board of commissioners, audit committee, transfer pricing, earnings management have an effect on tax avoidance, as well as to test the board of directors, board of commissioners, audit committee, transfer pricing, earnings management have an effect on tax avoidance with profitability as moderation. The population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange in the 2019-2022 period. The sampling technique used purposive sampling method and obtained a sample of 26 companies with a total sample of 104 financial statements. Data analysis used descriptive statistics and inferential statistics using SmartPLS 3.2.9 as a testing tool. The results of the study show that transfer pricing has a negative effect on tax avoidance. Board of directors, board of commissioners, audit committee, earnings management have no effect on tax avoidance. Profitability is not able to moderate the influence of the board of directors, board of commissioners, audit committee, transfer pricing and earnings management.